THE MAIN METHODS OF CORRECTING COMMUNICATIVE ACTIVITY IN CHILDREN WITH SPEECH IMPAIRMENT (American Journal of Interdisciplinary Research and Development, 2024)
The article highlights the main methods for correcting communicative activity in children with speech impairment. Effective rules of communication, hearing skills and work activity of a speech pathologist are analyzed.